Analysis of VAT collection, distribution, and audit of B-Trac Technologies Ltd. - Rashed, Sayed Raheduzzaman (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.